Evaluating the Role of Social Norms in Fostering Pro-Environmental Behaviors - Perry, George L.W.; Richardson, Sarah J.; Harré, Niki; Hodges, Dave; Lyver, Phil O’B.; Maseyk, Fleur J.F.; Taylor, Riki; Todd, Jacqui H.; Tylianakis, Jason M.; Yletyinen, Johanna; Brower, Ann (Frontiers in Environmental Science, 2021)
Human activity is changing the biosphere in unprecedented ways, and addressing this challenge will require changes in individual and community patterns of behavior. One approach to managing individual behaviors is “top-down” and involves imposing sanctions through legislative frameworks. However, of itself, a top-down framework does not appear sufficient to encourage the changes required to meet environmental sustainability targets. Thus, there has been interest in changing individual-level behavior from the “bottom-up” by, for example, fostering desirable pro-environmental behaviors via social norms. Social norms arise from expectations about how others will behave and the consequences of conforming to or departing from them. Meta-analyses suggest that social norms can promote pro-environmental behavior. Environmental social norms that appear to have changed in recent decades and have themselves promoted change include recycling, include nascent behavioral shifts such as the move away from single-use plastics and flight shaming (flygskam). However, whether the conditions under which pro-environmental social norms emerge and are adhered to align with environmental systems’ features is unclear. Furthermore, individuals might feel powerless in a global system, which can limit the growth and influence of pro-environmental norms. We review the conditions believed to promote the development of and adherence to social norms, then consider how those conditions relate to the environmental challenges of the Anthropocene. While promoting social norms has a valuable role in promoting pro-environmental actions, we conclude that norms are most likely to be effective where individual actions are immediately evident and have an obvious and local effect.